Electrochemical Reduction of CO2 With Good Efficiency on a Nanostructured Cu-Al Catalyst - Zeng, Juqin; Castellino, Micaela; Fontana, Marco; Sacco, Adriano; Monti, Nicolò B. D.; Chiodoni, Angelica; Pirri, Candido F. (Frontiers in Chemistry, 2022)
Carbon monoxide (CO) and formic acid (HCOOH) are suggested to be the most convenient products from electrochemical reduction of CO2 according to techno-economic analysis. To date, tremendous advances have been achieved in the development of catalysts and processes, which make this research topic even more interesting to both academic and industrial sectors. In this work, we report nanostructured Cu-Al materials that are able to convert CO2 to CO and HCOOH with good efficiency. The catalysts are synthesized via a green microwave-assisted solvothermal route, and are composed of Cu2O crystals modified by Al. In KHCO3 electrolyte, these catalysts can selectively convert CO2 to HCOOH and syngas with H2/CO ratios between 1 and 2 approaching one unit faradaic efficiency in a wide potential range. Good current densities of 67 and 130 mA cm−2 are obtained at −1.0 V and −1.3 V versus reversible hydrogen electrode (RHE), respectively. When switching the electrolyte to KOH, a significant selectivity up to 20% is observed for C2H4 formation, and the current densities achieve 146 and 222 mA cm−2 at −1.0 V and −1.3 V versus RHE, respectively. Hence, the choice of electrolyte is critically important as that of catalyst in order to obtain targeted products at industrially relevant current densities.